Proceedings of ADVED 2020- 6th International Conference on Advances in Education 2020
DOI: 10.47696/adved.202061
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Content Knowledge of Accounting Teachers in South Africa: Readiness of Grade 9 for Accounting in Grade 10

Abstract: EMS in grade 9 includes accounting related assessment standards upon which the grade 9 is a platform to prepare Grade 9 learners for Grade 10. especially Accounting curriculum builds. The main objective of the study was to determine pedagogical content knowledge and preparedness of Economic and Management Sciences teachers in preparing Grade 9 for Grade 10 in South Africa .Participants were a purposive sample five senior phase schools in Free State Province in Lejweleputswa District of South Africa were chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Several studies identified factors that can be associated with problems relating to content knowledge mastery of accounting teachers (Melo et al, 2020;Modise, 2016;Peter et al, 2017). These factors are classified as misconceptions, difficulties associated with defining accounting concepts, inability to manipulate accounting equations, and difficulty in applying accounting principles and procedures (Modise & Letlhoenyo, 2020). These studies confirm that misconceptions are generally undesirable and must be identified and addressed (Melo et al, 2020;Peter et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 72%
See 4 more Smart Citations
“…Several studies identified factors that can be associated with problems relating to content knowledge mastery of accounting teachers (Melo et al, 2020;Modise, 2016;Peter et al, 2017). These factors are classified as misconceptions, difficulties associated with defining accounting concepts, inability to manipulate accounting equations, and difficulty in applying accounting principles and procedures (Modise & Letlhoenyo, 2020). These studies confirm that misconceptions are generally undesirable and must be identified and addressed (Melo et al, 2020;Peter et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 72%
“…These studies report that teachers have limited accounting content knowledge because they are generalists rather than specialists (Nixon et al, 2015), and they choose to spend their time and effort teaching other subjects. Secondary school teachers have to complete a specialization in their specialty subject before teaching it (Modise & Letlhoenyo, 2020); the area of study is considered to be the teacher's area of expertise. In the senior phase, teachers are not required to have specialized in a subject, and it is doubtful whether teachers can show the same level of competence in all subjects (Modise, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations